PERSEPSI UMKM TERHADAP INSENTIF PAJAK DIMASA PANDEMI COVID-19 - Tania Nurfadillah; Ariya Kusumah Jaya; Irma Melawati; Roisatul Hidayah; Rovi Solihati (Journal of Taxation Analysis and Review, 2021)
This study aims to determine the perception of MSMEs on tax incentives during the Covid-19 pandemic. In approximately one year, the whole world is experiencing a major crisis due to a virus called corona or Covid-19 which caused a world pandemic. Indonesia is also one of the countries with the most virus cases in Asia. So that the government has taken various ways to reduce the spread of the Covid-19 virus, one of which is the implementation of Large-Scale Social Restrictions (PSBB), so that it has a wide impact on various business sectors to be hampered until it decreases, which causes an economic crisis, especially for MSMEs. The impact of this pandemic is also felt in the taxation sector. Where, taxes are a source of state revenue. The government issued a new policy on MSME tax incentives contained in PMK Number 44/PMK.03/2020, namely Final PPh based on Government-borne PP 23 (DTP). This policy aims to sustain MSME business, encourage public participation and knowledge of taxation. Qualitative data analysis techniques are carried out by collecting data, sorting data, presenting and analyzing data, and concluding data. Based on the results of in-depth interviews with five sources, it shows that they really appreciate the tax incentive policy.